Effect of sago waste, manure and straw biochar on peanut (Arachis hypogaea L.) growth and yield on an Ultisol of Southeast Sulawesi - E Tando; A Nugroho; T Islami (Brawijaya University, 2017)
Farmland in Southeast Sulawesi is largely dominated by Red and Yellow Podzolic soil type or Ultisol up to 60.30% of total soil. Aspects that caused low productivity, deteriorating soil physically and chemical properties in Ultisol soil is low soil organic matter content. Average peanut production in Southeast Sulawesi 2014 reached 0.46 t, on the other hand average domestic production is 1.87 t. The decrease in production is caused by decline in land productivity. Low peanut production is caused by soil fertility. Declining soil fertility can be restored by applying organic matter into the soil, but, in a tropical environment, the rate of organic matter decomposition and mineralization take place very quickly, resulting in additional organic material each planting season. Another alternative is to reduce the organic matter decomposition rate and release carbon in the soil through utilizing agricultural and animal waste into biochar which is resistant to corrosion. The experiment was conducted using a randomized block design which consisted of nine treatments and three replications. The results exhibited that straw biochar at 25%, or 2.48 t/ha + manure biochar at 75% equivalent to 5.87 t/ha was capable of increasing growth and yield rate for peanut varieties Talam 1 . Peanut varieties Talam 1 yield increased after sago waste , manure and straw application, by 45.62% compared to peanut crops yield without utilizing biochar on Ultisol.